Spectrophotometric study on binding of 2-thioxanthone acetic acid with ct-DNA - Ataci, Nese; Ozcelik, Elif; Arsu, Nergis (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Thioxanthone and its derivatives are the most remarkable molecules due to their vast variety of application such as radiation curing that is, until using them as a therapeutic drug. Therefore, in this study it was intended to use 2-Thioxanthone acetic acid with and without NaCl in Tris HCl buffer solution (pH:7.0) to represent the interaction with ct-DNA. The UV-vis absorption spectra of TXCH2COOH in the presence of ct-DNA showed hypochromism and the intrinstic binding constant (K-b) was determined as 6 x 10(3) L mol(-1). The fluoresence intensity of TXCH2COOH with ct-DNA clearly increased up to 101% which indicated that the fluorescence intensity was very sensitive to ct-DNA concentration. The binding constant (K) and the values of number of binding sites (n) and were calculated as 1.8 x 10(3) L mol(-1) and 0.69, respectively. When the quenching constants (K-sv) of free TXCH2COOH and TXCH2COOH, which were bonded with ct-DNA were compared, slightly changed values of Ksv were seen. Moreover, displacement assay with Hoechst 33,258 and viscosity measurements in the presence and absence of NaCl salt also confirmed the binding mode which noted the electrostatic interaction following groove binding between TXCH2COOH and ct-DNA. Last but not least, the salt effect was examined on ct-DNA binding with TXCH2COOH. The results of the experiments indicated that the groove binding was strengthened by NaCl whereas in the high NaCl concentration, the binding ability of TXCH2COOH to ct-DNA was inversely affected. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: 2-Thioxanthone acetic acid; Ct-DNA; Binding; Electrostatic interaction; Groove binding; CALF THYMUS-DNA; FREE-RADICAL POLYMERIZATION; N-ALKYL SULFATES; VISIBLE PHOTOINITIATOR; II PHOTOINITIATOR; THIOXANTHONE; HOECHST-33258; MODES; LIGHT; PROBE; Spectroscopy